Controversy of the Liberal-Islamic Thought about Pluralism of Religions in Indonesia - Samsudin, Samsudin; Zakaria, Mumuh Muhsin (TAWARIKH, 2017)
ABSTRACT: To enter into the religious pluralism of thought, in which the Muslims need to do, is to reinterpret the teachings of Islam, so that the Muslims do not happen with the authoritarian attitudes that consider the most of uncorrect in understanding of Islam. The word of plural and pluralism means diversity and plurality. Thus, the notion of pluralism can be defined as an ideology that recognizes diversity in its various aspects, for example in understanding of religion, culture, and geography. This study tries to elaborate the controversy of the liberal-Islamic thought about pluralism of religions in Indonesia. By using the qualitative methods, especially the historical approach with descriptive analysis, this study concerns on the controversy of Islamic liberal thought in one hand; and, in other hand, its relevances to religious pluralism in Indonesianâs social and political context. The findings show that pluralism of religions by liberal Islamic group that all religions with its variations and levels of different depths are the same as the road of religious. This opinion has caused controversy, because there is criticism and there were strongly rejected the idea of pluralism of the liberal Islam. As K.H. Atiyan Ali M. Daâi (2002) and MUI (Indonesian Ulema Council) issued a âfatwaâ that pluralism is unlawful, because it has a tendency considers all religions that difference could be reduced or avoided, if the same understanding of pluralism.Â KEY WORDS: Controversial Issues; Liberal Islamic Thought; Understanding of Islam; Pluralism of Religions; Indonesian Islam.Â Â Â About the Authors: Samsudin, M.Ag. is a Postgraduate Student of UNPAD (Padjadjaran University) Bandung and a Lecturer at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, West Java, Indonesia. Dr. Mumuh Muhsin Zakaria is a Senior Lecturer at the Department of History, Faculty of Humanities UNPAD Bandung, West Java, Indonesia. Corresponding authors is: samsudin_1970@yahoo.comRecommended Citation: Samsudin & Mumuh Muhsin Zakaria. (2017). âControversy of the Liberal-Islamic Thought about Pluralism of Religions in Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.71-80. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Article Timeline: Accepted (August 17, 2017); Revised (September 19, 2017); and Published (October 28, 2017).